THE EFFECT OF INFLATION AND INVESTMENT ON OPEN UNEMPLOYMENT IN INDONESIA - Dewi Ernita (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the effect of inflation and investment on open unemployment in Indonesia in 2009-2023 partially and simultaneously. The research method uses multiple linear regression analysis with secondary data from Indonesia in Figures for the period 2009-2023. The results of the study indicate that partially Inflation has no effect on Open Unemployment in Indonesia in 2009-2023, because tcount < ttable (-1.712 < 2.17881). and Investment has a significant effect on Open Unemployment in Indonesia in 2009-2023, because tcount > ttable (-3.054 > 2.17881). Simultaneously Inflation and Investment have a significant effect on Open Unemployment in Indonesia in 2009-2023, because tcount > ttable (4.663 > 3.89)